2002
DOI: 10.1007/s00134-002-1524-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prone position on hepato-splanchnic hemodynamics in acute lung injury

Abstract: P2Model-based neuro-fuzzy control of FiO 2 for intensive care mechanical ventilation HF Kwok, GH Mills, M Mahfouf, DA Linkens Introduction: In our experience, very often, even with a nonrebreathing mask (NRM), high oxygen delivery to patient with the existent materials is insufficient. However, many of these patients need high oxygen therapy for a limited period of time. In this study we report our experience with a new device that serves to increase the concentration of oxygen delivered by a classical nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 25 publications
1
22
2
Order By: Relevance
“…However, taking our results in conjunction with those of other studies it would appear that prone ventilation does not appear to increase IAP [3,4]. Whether prone ventilation has a future role in the management of acute lung injury/ARDS is another matter.…”
Section: Discussioncontrasting
confidence: 35%
See 3 more Smart Citations
“…However, taking our results in conjunction with those of other studies it would appear that prone ventilation does not appear to increase IAP [3,4]. Whether prone ventilation has a future role in the management of acute lung injury/ARDS is another matter.…”
Section: Discussioncontrasting
confidence: 35%
“…We felt that the choice of mid-axillary line would reveal changes in IAP more meaningfully, even though the absolute values may be more difficult to interpret. This approach has been used by other investigators [4].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some showed that prone positioning had no or minimal effect on cardiac output [24,28-30] but they were conducted under different ventilator settings [24,[28][29][30] and/or a long time after prone positioning [24,28]. On the contrary, others have reported increased cardiac output with prone positioning [9,10].…”
Section: Prone Positioning May Increase Cardiac Outputmentioning
confidence: 95%